Investigation of ischemia modified albumin, oxidant and antioxidant markers in acute myocardial infarction - Hazini, Ahmet; Cemek, Mustafa; Işıldak, İbrahim; Alpdağtaş, Saadet; Önül, Abdullah; Şenel, Ünal; Kocaman, Tuba; Dur, Ali; Iraz, Mustafa; Uyarel, Hüseyin (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Introduction : Acute myocardial infarction (AMI) is still one of the most common causes of death worldwide. In recent years, for diagnosis of myocardial ischemia, a new parameter, called ischemia modified albumin (IMA), which is thought to be more advantageous than common methods, has been researched. Aim : In this study, systematic analysis of parameters considered to be related to myocardial ischemia has been performed, comparing between control and myocardial ischemia groups. Material and methods : We selected 40 patients with AMI and 25 healthy controls for this study. Ischemia modified albumin levels, glutathione peroxidase (GPx), superoxide dismutase (SOD), and catalase (CAT) antioxidant enzyme activities and non-enzymatic antioxidants such as retinol, α=-tocopherol, β-carotene and ascorbic acid levels were investigated in both groups. Glutathione (GSH) and malondialdehyde (MDA) levels, which are indicators of oxidative stress, were compared between patient and control groups. Results : Ischemia modified albumin levels were found significantly higher in the AMI diagnosed group when compared with controls. The MDA level was elevated in the patient group, whereas the GSH level was decreased. SOD, GPx and CAT enzyme levels were decreased in the patient group, where it could be presumed that oxidative stress causes the cardiovascular diseases. Conclusions : Due to the increased oxidative stress, non-enzymatic and enzymatic antioxidant capacity was affected. Systematic investigation of parameters related to myocardial infarction has been performed, and it is believed that such parameters can contribute to protection and early diagnosis of AMI and understanding the mechanism of development of the disease.